Luminescent Porous Polymers Based on Aggregation‐Induced Mechanism: Design, Synthesis and Functions. Issue 47 (14th October 2016) - Dalapati, Sasanka; Gu, Cheng; Jiang, Donglin
Abstract : Enormous research efforts are focusing on the design and synthesis of advanced luminescent systems, owing to their diverse capability in scientific studies and technological developments. In particular, fluorescence systems based on aggregation‐induced emission (AIE) have emerged to show great potential for sensing, bio‐imaging, and optoelectronic applications. Among them, integrating AIE mechanisms to design porous polymers is unique because it enables the combination of porosity and luminescence activity in one molecular skeleton for functional design. In recent years rapid progress in exploring AIE‐based porous polymers has developed a new class of luminescent materials that exhibit broad structural diversity, outstanding properties and functions and promising applications. By classifying the structural nature of the skeleton, herein the design principle, synthetic development and structural features of different porous luminescent materials are elucidated, including crystalline covalent organic frameworks (COFs), metal‐organic frameworks (MOFs), and amorphous porous organic polymers (POPs). The functional exploration of these luminescent porous polymers are highlighted by emphasizing electronic interplay within the confined nanospace, fundamental issues to be addressed are disclosed, and future directions from chemistry, physics and materials science perspectives are proposed. Abstract : Porous skeletons provide a unique molecular platform for designing photoluminescent materials . Here, the progress and recent achievements in developing new design principles and synthetic strategies for AIE‐based porous luminescent materials are summarized. Cutting‐edge functions are designed, fundamental issues that need to be addressed presented, and future directions from chemistry, physics, and materials perspectives are predicted.